Herança da resistência do acesso AC-09 de meloeiro a Podosphaera xanthii - Tomaz, Francisco Linco de Souza (Universidade Federal Rural do Semi-Árido, 2017)
Commercial production of melon (Cucumis melo L.) in Brazil started in the 60’s, however the humidity and temperatures conditions of producing regions limited yield and fruits’ quality. Since then, melon production in Brazilian Northeast has increased considerably. Currently, the Northeast is responsible for about 99% of the total exported. Associated with the crop development, there are some phytopathological problems that reduce production and quality of fruits. Among these problems, the occurrence of Powdery mildew stands out, disease caused by the fungal species Podosphaera xanthii. Powdery mildew is the most important fungal disease that attacks aerial parts of melon plants in the world. The disease is characterized by white powdery spots that correspond to the reproductive structures of the fungus. The powdery mildew reduces crop yield due to reduction in foliar area for photosynthesis. Despite the efficiency, the use of fungicides cause problems related to selection of resistant pathogen strains and contamination of environment, fruit and worker. On the other hand, the use of resistant cultivars has been shown as a promising method to control powdery mildew in melon. The obtention of resistant cultivars is made by introgression of resistant alleles. This present research aimed to study the inheritance of resistance of AC-09 access in melon plants by breeding with ‘Védrantais’ susceptible cultivar, in greenhouse conditions. Completely randomized design was used, where plots were formed according to the number of plants required in each population. All plants were classified as resistant or susceptible based in a scale of scores. Segregation ratio of resistance/susceptibility observed in different populations (F1, F2, RC1, and RC2) indicates that the inheritance of resistance of AC-09 access to Podosphaera xanthii is monogenic and dominant.
Monografia
Keywords: Controle genético; Cucumis melo; Monogênica; Oídio; Genetic control; Cucumis melo; Monogenic; Genetic control. Cucumis melo. . Powdery mildew; CIENCIAS AGRARIAS::AGRONOMIA